Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1994
DOI: 10.1039/an9941901277
|View full text |Cite
|
Sign up to set email alerts
|

Wide-spread and systematic errors in the analysis of soils for polychlorinated biphenyls. Part 1. A review of inter-laboratory studies

Abstract: The determination of polychlorinated biphenyls in soils is one of the most widely performed tests among environmental laboratories. It is a very difficult test and is subject to a great deal of inter-laboratory variance and bias. A new inter-laboratory study, using five soils spiked at four different concentrations with Aroclor 1260, was conducted with two groups of laboratories numbering 20 and 129, respectively. The results of this study are compared with the results of the other studies but show that the bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1995
1995
2000
2000

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…The PCB ELISA results for Soxhlet extracts are biased low, on the average, by a factor of about 0.83. The Soxhlet/ELISA and Method 8081 results are equivalent from a practical standpoint, as a 17% bias is negligible; interlab bias of such a magnitude is commonly observed, even when using the same method. , In the present case of comparing the PCB ELISA data to Method 8081 data, not only is an intermethod comparison being made, but a confounding interlab comparison is being made as well. It can thus be concluded that the PCB ELISA provided accurate results when coupled to an appropriate extraction procedure.…”
Section: Resultsmentioning
confidence: 92%
“…The PCB ELISA results for Soxhlet extracts are biased low, on the average, by a factor of about 0.83. The Soxhlet/ELISA and Method 8081 results are equivalent from a practical standpoint, as a 17% bias is negligible; interlab bias of such a magnitude is commonly observed, even when using the same method. , In the present case of comparing the PCB ELISA data to Method 8081 data, not only is an intermethod comparison being made, but a confounding interlab comparison is being made as well. It can thus be concluded that the PCB ELISA provided accurate results when coupled to an appropriate extraction procedure.…”
Section: Resultsmentioning
confidence: 92%
“…[1][2] PCB analysis is usually carried out using gas chromatography equipped with an electron capture detector, although other detecting strategies (e.g., mass spectrometry) are used. 3 These techniques require expensive instrumentation, and usually the analysis procedure is quite long.…”
Section: Introductionmentioning
confidence: 99%
“…The determination of trace levels of these organic compounds is a complicated procedure, consisting of many steps-sample homogenisation, extraction from the matrix, clean-up and concentration, gas chromatographic separation and detection-each of which can significantly contribute to the total error in the final determination. [1][2][3][4][5][6][7][8][9] The clean-up procedure has proved fundamental in removing interferences and increasing the accuracy and precision of the final result. 1,9 Co-extracted compounds can interfere with the final determination of PCBs, since contamination can overload a high-resolution gas chromatographic (HRGC) column, create negative peaks or an erratic response when electron-capture detection (ECD) is used, or can lead to co-elution with PCBs, resulting in misidentification and incorrect determination.…”
mentioning
confidence: 99%
“…A number of interlaboratory studies have been organised with the following objectives: to determine variations in PCB determinations; to identify what sources cause these variations; and to reduce them through a step-by-step learning process. [2][3][4][5][6][7][8] The sources of systematic, random errors produced by the various steps in the method can be evaluated by following the traceability chain of the analytical procedure in detail. [10][11][12] In particular, the different validation methods determine the loss of selected target compounds (single PCB congener method) and possible interferences introduced in the subsequent analysis steps.…”
mentioning
confidence: 99%